A functional clock in only two dorsal clock neurons is sufficient to restore the basal circadian activity pattern of Drosophila melanogaster - Nils Reinhard; Enrico Bertolini; Takuya Kuwahara; Manabu Sekiguchi; Dirk Rieger; Weihua Li; Paul H. Taghert; Taishi Yoshii; Charlotte Helfrich-Förster (Proceedings of the National Academy of Sciences, 2025)
Circadian clocks form complex networks to orchestrate the behavior and physiology of animals. Elucidating the organization of these clock networks is critical to understanding how circadian clocks achieve robust timing. Clock neurons have been best characterized in the model organism Drosophila melanogaster . At the early stages of development, Drosophila has a clock network consisting of only nine neurons per hemisphere. This set of clock neurons consists of lateral and dorsal neurons and persists in the adult fly, in which the clock network is greatly expanded to a total of ~240 neurons. The function of the early-born lateral clock neurons is well established in the adult fly. They control morning and evening activity and are responsible for circadian rhythmicity under constant conditions. Only recent studies have begun to dissect the function of the dorsal clock neurons. Using clock rescue experiments, we show here that a functional clock in only four of them, the DN 1a , is sufficient to restore a bimodal locomotor activity pattern and rhythmic activity under constant conditions in the adult fly. This is achieved by CCHamide-1 signaling most likely to the lateral morning neurons, which are considered the main pacemakers of the clock, and by glutamate signaling to the lateral evening neurons. Interestingly, all the neurons involved are part of the early-born clock network, strongly suggesting that a core clock is already formed during early development. This set of clock neurons appears sufficient in the adult fly to drive the basal circadian activity pattern.